A Professional Approach to Translator Training (PATT) - Olvera Lobo, María Dolores; Robinson, Bryan; Castro Prieto, Rosa María; Quero Gervilla, Enrique; Muñoz Martín, Ricardo; Muñoz Raya, Eva; Murillo Melero, Miguel; Senso Ruiz, José Antonio; Vargas Quesada, Benjamín; Díez Lerma, José Luis (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2007)
AbstractInformation technology is a significant challenge for teachers involved in training translators, the prototype of teleworking professions. This article presents an approach that integrates technology into the day-to-day teaching of a range of disciplines. The University of Granada, Spain, offers a four-year first-degree program in Translation and Interpreting. The innovative, collaborative learning project we describe is an online simulation of work in a translation agency. We believe it enhances the quality of translator training within the university context.